The relationship between serum pregnancy-associated plasma protein-A level in patients with aortic valve stenosis: a case-control study. Issue 6 (3rd September 2021) - Girgin, E. Merve; Colak, Ayfer; Simsek, Ersin Cagri; Toprak, Burak; Yalcin, Hülya; Ozdogan, Oner; Duman, Can
Abstract: Objective: Calcific aortic stenosis (AS) is the most common form of calcific aortic valve disease. Many matrix metalloproteinase (MMP) have been shown to be expressed in aortic sclerosis and contribute to valve fibrosis and calcification. We investigated the relationship between Pregnancy-Associated Plasma Protein-A (PAPP-A) and AS. Methods: Sixty-one patients who referred to our cardiology clinic having AS diagnosed with transthoracic echocardiography and thirty control subjects were included in this study. The patient group was divided into two groups as mild and moderate-severe AS in terms of echocardiography results. Levels of C-reactive protein (CRP), insulin-like growth factor-1 (IGF-1) and PAPP-A were measured. Results: There was statistically significant difference between the patient and control group for PAPP-A ( p = 0.009). In addition, the difference between MPV, IGF-1 and PAPP-A levels of control and AS groups was found. We found that serum PAPP-A level was an independent predictor of AS ( B = 0.107, p = 0.01) by logistic regression analysis. In linear regression analysis, a significant correlation was found for AS severity with MPV, IGF-1 and PAPP-A levels, respectively ( p = 0.025, p = 0.004, p = 0.035). It was revealed that PAPP-A and IGF-1 were negatively correlated ( r = −0.327, p = 0.002). Correlation of serum PAPP-A level with echocardiographic parameters was no observed. Conclusion: The level of PAPP-A may be a marker used in diagnosis rather than a marker used to determine the severity of AS. Studies with larger patient populations may further explain the role of PAPP-A in the diagnosis and treatment of AS.